Pengaruh Pajak Daerah dan Belanja Pemerintah Terhadap Pertumbuhan Ekonomi di Provinsi Aceh Tahun 2008 - 2018 - Mirza Sayuti; Rizki Maulana; Kayyis Rifqan; Abrar (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This research was conducted in Aceh province for the 2008-2018 period. The aim of this research is to determine the influence of regional taxes and government spending on economic growth in Aceh province in 2008-2018. This research uses secondary data for the 2008-2018 period sourced from the Central Statistics Agency and the Aceh Financial Management Agency. In this study, time series linear regression analysis was used using the eviews 9 analysis tool. The data used was 11 year time series data. Based on the results of tests carried out with probability on variables, it can be concluded that regional taxes and government spending have a positive and significant influence on economic growth in the narrow sense in Indonesia. From the results of the data regression carried out, the R2 (Coefficient of Determination) value is 0.689762, this means that 68.97% of GRDP at constant prices in Aceh province can be explained by regional tax and government spending variables, while the remainder is 31.03% influenced by other variables.